Bobot Karkas dan Giblet Ayam Broiler dengan Penambahan Pakan Fermentasi Kelakai dan Dedak Padi pada Pakan Komersil - Herlinae Herlinae; Maria Erviana Kusuma; Yulli Yulli (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
This study aims to determine the effect of the addition of fermented kelakai and rice bran to commercial feed on carcass and giblet weight of broiler chickens and to determine the level of addition of fermented kelakai and rice bran to commercial feed which gives the best results on chicken carcass and giblet weight. broilers. This research was conducted at the practice location of the Faculty of Animal Husbandry, Christian University of Palangka Raya, Jalan G.S Rubay Palangka Raya. This study was designed using a completely randomized design (CRD) with a single treatment of various additions of fermented feed and rice bran to commercial feed with 5 repetitions, namely Treatment A = Fermentation Kelakai 0% + BR 100%, Treatment B = Fermentation 2,5% + 100% BR, Treatment C = Fermentation Kelakai 5% + 100% BR, Treatment D = Fermentation Kelakai 7,5% + 100% BR. The results of this study were the addition of fermented kelakai and rice bran had no effect on carcass and giblet weight of broiler chickens. Keywords : Fermented feed, kelakai, carcass, giblet, broiler chicken